Survival of antibiotic resistant Escherichia coli in vacuum-packed keropok lekor: Food safety alert among SME keropok lekor producers - Wan-Hamat, H.; Lani, M. N.; Hamzah, Y.; Alias, R.; Hassan, Z.; Mahat, N. A. (Malaysian Soc Parasitology Tropical Medicine, 2024)
The microbiological quality of thirty ready-to-eat (RTE) keropok lekor (a sausage shape Malaysian fish product) was evaluated in comparison to microbiological guidelines for ready to eat foods. The two E. coli isolates were subjected to DNA sequencing, identified and tested for their resistance towards fifteen different antibiotics. The survival and growth of the isolated E. coli strains inoculated in keropok lekor at atmospheric air and vacuum packaging were also evaluated. Results revealed that four samples (13.33%) contained Enterobacteriaceae counts that exceeded the recommended allowable counts of 4.0 log(10) CFU/g. Unsatisfactory level of coliforms (> 1.7 log(10) CFU/g) was also observed in ten of the samples; two of which contained E. coli (2.1 +/- 0.17 and 3.7 +/- 0.02 log(10) CFU/g), suggesting of poor hygiene and sanitation practices. While the 'Possible E10' E. coli strain was observably resistant towards Nalidixic acid (30 mu g) alone, B10 E. coli isolate was worryingly resistant towards Ampicillin (10 mu g), Ceftazidime (30 mu g), Ciprofloxacin (5 mu g), Ceftriaxone (30 mu g), Nalidixic acid (30 mu g) and Tetracycline (30 mu g). This study also revealed that the growth and survival of the 'Possible E10' and B10 E. coli strains were not significantly affected by vacuum packaging when stored at both 4 degrees C and 28 degrees C. Therefore, intervention programmes to alert and educate small-medium enterprisers (SMEs) of keropok lekor producers on food safety as well as potential health risks that can be associated due to inappropriate handling procedures of such product, merits consideration.